On the local behavior of Sobolev classes on two-dimensional Riemannian manifolds - Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.9 We study open discrete maps of two-dimensional Riemannian manifolds from the Sobolev class. For these mappings,we obtain the lower estimates of distortions of the moduli of the families of curves. As a consequence, we establish theequicontinuity of Sobolev classes at interior points of the domain.